HUBUNGAN TINGKAT KECEMASAN DENGAN KUALITAS TIDUR PADA PASIEN YANG MENJALANI HEMODIALISIS DI RUMAH SAKIT KHUSUS GINJAL RASYIDA MEDAN - Damanik, Veronica Anggreni (Universitas Prima Indonesia, 2020)
Hemodialysis is the process of removing metabolic waste substances, other toxic substances through a dialiser that functions as an artificial kidney. Hemodialysis or dialysis is the transfer of the patient's blood from his body which occurs in disfusion and ultrafiltration. This study aims to determine the relationship between the level of anxiety and sleep quality in patients undergoing hemodialysis at Rasyida Kidney Special Hospital Medan. This research design used analytical survey with cross sectional approach. The sampling technique was accidental sampling, a sample of 75 respondents. The data used are primary data by distributing questionnaires, secondary data, and tertiary data while the data analysis used is univariate analysis and bivariate analysis with Chi-Square test. The results of this study with stastic test showed that the p-value result was 0.033 (<α 0.05), so there was a relationship between the level of anxiety and the quality of sleep of patients undergoing hemodialysis in the Rasyida Kidney Special Hospital Medan. The conclusions in this study indicate that there is a significant correlation between the level of anxiety and sleep quality in patients undergoing hemodialysis in Medan Renalida Kidney Special Hospital. It is recommended for patients to control anxiety so that sleep quality will be better and recommended to health workers especially hemodialysis nurses to further enhance the knowledge of patients who increase hemodialysis by providing education/health education related to the effects and complications of hemodialysis.